CRISPR/Cas9-induced modification of the conservative promoter region of VRN-A1 alters the heading time of hexaploid bread wheat - Miroshnichenko, Dmitry; Timerbaev, Vadim; Klementyeva, Anna; Pushin, Alexander; Sidorova, Tatiana; Litvinov, Dmitry; Nazarova, Lubov; Shulga, Olga; Divashuk, Mikhail; Karlov, Gennady; Salina, Elena; Dolgov, Sergey (Frontiers in Plant Science, 2022)
In cereals, the vernalization-related gene network plays an important role in regulating the transition from the vegetative to the reproductive phase to ensure optimal reproduction in a temperate climate. In hexaploid bread wheat (Triticum aestivum L.), the spring growth habit is associated with the presence of at least one dominant locus of VERNALIZATION 1 gene (VRN-1), which usually differs from recessive alleles due to mutations in the regulatory sequences of the promoter or/and the first intron. VRN-1 gene is a key regulator of floral initiation; various combinations of dominant and recessive alleles, especially VRN-A1 homeologs, determine the differences in the timing of wheat heading/flowering. In the present study, we attempt to expand the types of VRN-A1 alleles using CRISPR/Cas9 targeted modification of the promoter sequence. Several mono- and biallelic changes were achieved within the 125-117 bp upstream sequence of the start codon of the recessive vrn-A1 gene in plants of semi-winter cv. ‘Chinese Spring’. New mutations stably inherited in subsequent progenies and transgene-free homozygous plants carrying novel VRN-A1 variants were generated. Minor changes in the promoter sequence, such as 1–4 nucleotide insertions/deletions, had no effect on the heading time of plants, whereas the CRISPR/Cas9-mediated 8 bp deletion between −125 and −117 bp of the vrn-A1 promoter shortened the time of head emergence by up to 2-3 days. Such a growth habit was consistently observed in homozygous mutant plants under nonvernalized cultivation using different long day regimes (16, 18, or 22 h), whereas the cold treatment (from two weeks and more) completely leveled the effect of the 8 bp deletion. Importantly, comparison with wild-type plants showed that the implemented alteration has no negative effects on main yield characteristics. Our results demonstrate the potential to manipulate the heading time of wheat through targeted editing of the VRN-A1 gene promoter sequence on an otherwise unchanged genetic background.